Four versus six cycles of CHOP chemotherapy in combination with six applications of rituximab in patients with aggressive B-cell lymphoma with favourable prognosis (FLYER): a randomised, phase 3, non-inferiority trial. Issue 10216 (21st December 2019) - Poeschel, Viola; Held, Gerhard; Ziepert, Marita; Witzens-Harig, Mathias; Holte, Harald; Thurner, Lorenz; Borchmann, Peter; Viardot, Andreas; Soekler, Martin; Keller, Ulrich; Schmidt, Christian; Truemper, Lorenz; et al.
Summary: Background: Six cycles of R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone) are the standard treatment for aggressive B-cell non-Hodgkin lymphoma. In the FLYER trial, we assessed whether four cycles of CHOP plus six applications of rituximab are non-inferior to six cycles of R-CHOP in a population of patients with B-cell non-Hodgkin lymphoma with favourable prognosis. Methods: This two-arm, open-label, international, multicentre, prospective, randomised phase 3 non-inferiority trial was done at 138 clinical sites in Denmark, Israel, Italy, Norway, and Germany. We enrolled patients aged 18–60 years, with stage I–II disease, normal serum lactate dehydrogenase concentration, ECOG performance status 0–1, and without bulky disease (maximal tumour diameter <7·5 cm). Randomisation was computer-based and done centrally in a 1:1 ratio using the Pocock minimisation algorithm after stratification for centres, stage (I vs II), and extralymphatic sites (no vs yes). Patients were assigned to receive either six cycles of R-CHOP or four cycles of R-CHOP plus two doses of rituximab. CHOP comprised cyclophosphamide (750 mg/m 2 ), doxorubicin (50 mg/m 2 ), and vincristine (1·4 mg/m 2, with a maximum total dose of 2 mg), all administered intravenously on day 1, plus oral prednisone or prednisolone at the discretion of the investigator (100 mg) administered on days 1–5. Rituximab was given at a dose of 375 mg/m 2 of body surface area. Cycles were repeated every 21 days. No radiotherapy was planned except for testicular lymphoma treatment. The primary endpoint was progression-free survival after 3 years. The primary analysis was done in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of assigned treatment. A non-inferiority margin of −5·5% was chosen. The trial, which is completed, was prospectively registered at ClinicalTrials.gov, NCT00278421 . Findings: Between Dec 2, 2005, and Oct 7, 2016, 592 patients were enrolled, of whom 295 patients were randomly assigned to receive six cycles of R-CHOP and 297 were assigned to receive four cycles of R-CHOP plus two doses of rituximab. Four patients in the four-cycles group withdrew informed consent before the start of treatment, so 588 patients were included in the intention-to-treat analysis. After a median follow-up of 66 months (IQR 42–100), 3-year progression-free survival of patients who had four cycles of R-CHOP plus two doses of rituximab was 96% (95% CI 94–99), which was 3% better (lower limit of the one-sided 95% CI for the difference was 0%) than six cycles of R-CHOP, demonstrating the non-inferiority of the four-cycles regimen. 294 haematological and 1036 non-haematological adverse events were documented in the four-cycles group compared with 426 haematological and 1280 non-haematological adverse events in the six-cycles group. Two patients, both in the six-cycles group, died during study therapy. Interpretation: In young patients with aggressive B-cell non-Hodgkin lymphoma and favourable prognosis, four cycles of R-CHOP is non-inferior to six cycles of R-CHOP, with relevant reduction of toxic effects. Thus, chemotherapy can be reduced without compromising outcomes in this population. Funding: Deutsche Krebshilfe.